Regional Tourism Management in Increasing Regional Original Income Reviewed From the Perspective of the Business Cooperation Law - Agustini, Dewa Ayu Eka; Adnyani, Ni Ketut Sari; Myartawan, I Putu Ngurah Wage; Saputra, I Nyoman Pasek Hadi (Jurnal Ilmiah Sains Sosial, Kewirausahaan dan Kebudayaan, 2024)
The purpose of this study was to examine the nature of regional government authority over regional tourism management business cooperation agreements and the legal consequences of regional tourism management business cooperation agreements in increasing Regional Original Income. This study uses normative legal research methods with statutory and conceptual approaches. The results of the study show that the regional government's authority in the field of tourism is in principle one of the implementation of the government's choice of affairs which is the authority of the Regency/City Regional Government, this is based on the provisions of Article 12 paragraph (3) letter b of Law no. 23 of 2014 concerning Regional Government, but specifically the authority of the Regency Government in the field of tourism is regulated in the provisions of Article 30 of Law no. 10 of 2009 concerning Tourism. The regulation of regional tourism business licensing has legal consequences for local governments to carry out tourism business licensing as a preventive juridical effort as an administrative instrument in the tourism business in increasing Regional Original Income.